Would the Addition of Immunotherapy Impact the Prognosis of Patients With Malignant Pericardial Effusion? - Chiruvella, Varsha; Ullah, Asad; Elhelf, Islam; Patel, Nikhil; Karim, Nagla Abdel (Frontiers in Oncology, 2022)
Pericardial effusion is a common finding in advanced-stage lung cancer. The presence of malignant cells or drainage of exudate effusion in the pericardial space may cause symptoms of dyspnea, pleuritic chest pain, and syncope. In addition to the difficulty physicians’ face in the detection and diagnosis of malignant pericardial effusion, treatment may be challenging considering the patient’s cancer prognosis and cardiovascular stability. Despite the availability of several treatment modalities for malignant pericardial effusion, including chemotherapy and surgery, patients with lung cancer historically present with poor prognosis. In addition to lung adenocarcinoma with malignant pericardial effusion, this case was complicated by COVID-19 and malignancy-associated obstructive pneumonia. We present a case of a 64-year-old woman with advanced non- small cell lung carcinoma (NSCLC) with malignant pericardial effusion who, despite testing positive for COVID-19 and having obstructive pneumonia, has favorable outcomes following systemic therapy with combined chemo-immunotherapy.